Partial discharges characteristics study in XLPE cable insulation with multiple defects - I. V. Komarov; D. A. Polyakov; K. I. Nikitin (Омский научный вестник)
The paper simulates the electric field intensity picture in the cable with one and several defects. Modeling has shown that the presence of several closely spaced defects does not lead to an increase in the electric field intensity in comparison with one defect. On the basis of experimental studies, an analysis of defects' number influence on various parameters of partial discharges (PD) is performed. Artificial defects are created in the area of the XLPE-insulated cable termination. The following parameters of PD are measured: the magnitude of the apparent charge, the power (intensity) of partial discharges, the phase-resolved partial discharge (PRPD) patterns, the shape of PD signals. The analysis shows an increase in the number of defects does not affect the characteristics of partial discharges, despite the fact the defects are located in different sections of the cable with distributed parameters. Thus, it can be difficult to quantify defects during cable partial discharge measurements.